Pedagogical Strategies and Teachers’ Instructional Experiences in Teaching Early Numeracy Skills in Public Elementary Schools of Maddela II District, Schools Division of Quirino - binwag, joan; Macalling, Madelyn (Studies in Technology and Education, 2026)
Abstract Early numeracy skills serve as foundational competencies that significantly influence learners’ future mathematical understanding, academic achievement, and problem-solving abilities. Teachers play a crucial role in developing these foundational skills through appropriate pedagogical strategies, learner-centered instruction, and contextualized classroom practices. This qualitative phenomenological study explored the pedagogical strategies and instructional experiences of teachers in teaching early numeracy skills in public elementary schools of Maddela II District, Schools Division of Quirino. Specifically, the study examined teachers’ instructional practices, classroom experiences, challenges encountered, coping mechanisms, and professional perspectives in teaching early numeracy among primary learners. Twelve public elementary school teachers handling Kindergarten to Grade 3 Mathematics classes were purposively selected as participants. Data were gathered through semi-structured interviews, classroom observations, and document analysis of lesson plans and instructional materials. Braun and Clarke’s thematic analysis framework was utilized in analyzing the collected data. Findings revealed that teachers employed contextualized, manipulative-based, and learner-centered pedagogical approaches to enhance learners’ numeracy development. Participants utilized games, visual aids, collaborative activities, concrete learning materials, and differentiated instruction to facilitate mathematical understanding and learner engagement. However, teachers also encountered challenges related to learners’ varied abilities, insufficient instructional materials, parental support limitations, and time constraints in addressing foundational numeracy gaps. Despite these difficulties, teachers demonstrated adaptability, instructional creativity, and professional commitment through remediation activities, peer collaboration, and continuous pedagogical improvement. The study concluded that effective early numeracy instruction requires strengthened institutional support, contextualized instructional resources, parental involvement, and continuous teacher professional development programs. The findings contribute to the growing discourse on foundational Mathematics education and early childhood pedagogy in Philippine elementary schools.